TINJAUAN YURIDIS TENTANG PROSES PEMBUKTIAN TINDAK PIDANA OLEH ANAK MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK: (Putusan Nomor 6/Pid.Sus-Anak/2022/PN Psw) - Done, Hardi; Samaluddin, Samaluddin; Wahyudi, Arif (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2024)
From the research results, the process of proving child crimes is different from proving general crimes (adult criminal cases). The process of proving child criminal acts is regulated in Law Number. 11 of 2012 concerning the Juvenile Criminal Justice System. In terms of evidence to prove children's cases, it is not specifically regulated in the SPPA Law, therefore it still refers to the Criminal Procedure Code (KUHAP) Article 184. The absence of guidelines for implementing diversion practices for law enforcement officers has caused the implementation of diversion to vary depending on understanding of law enforcement officers and lack of understanding in the implementation of the SPPA Law by law enforcement officers.